The role of creative communications and gamification in customer engagement in higher education: A sentiment analysis approach - Bilro, R. G.; Loureiro, S. M. C.; Angelino, F. J. (Journal of Creative Communications, 2022)
This paper aims to explore gamification tools in services and higher education environments and their role in creating student engagement. The research adopts a qualitative method based on quasi-experimental design. Participants from a higher education institution are exposed to gamification activities during a full semester. Researchers use sentiment analysis technique based on a text-mining approach to analyse the data. Findings reveal that participants perceive gamification in service settings as a useful tool. The global sentiment analysis reveals a positive sentiment about the gamification approach that contributes to increasing participants’ engagement. This study’s novelty arises from quasi-experimental research to measure gamification activities’ impact on students’ engagement, measured through sentiment analysis of their opinions.